2014
DOI: 10.3389/fnbeh.2014.00389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep deprivation on different phases of memory in the rat: dissociation between contextual and tone fear conditioning tasks

Abstract: Numerous studies show that sleep deprivation (SD) impacts negatively on cognitive processes, including learning and memory. Memory formation encompasses distinct phases of which acquisition, consolidation and retrieval are better known. Previous studies with pre-training SD induced by the platform method have shown impairment in fear conditioning tasks. Nonetheless, pre-training manipulations do not allow the distinction between effects on acquisition and/or consolidation, interfering, ultimately, on recall of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Finally, Experiment 3 provided support for the hypothesis that sleep deprivation would impair hippocampus-dependent contextual, but not amygdala-mediated cue, fear memory. This finding is consistent with other work that demonstrates that sleep deprivation targets contextual, but not cued, fear memory with shock as reinforcement [101] [104] [106] [142].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, Experiment 3 provided support for the hypothesis that sleep deprivation would impair hippocampus-dependent contextual, but not amygdala-mediated cue, fear memory. This finding is consistent with other work that demonstrates that sleep deprivation targets contextual, but not cued, fear memory with shock as reinforcement [101] [104] [106] [142].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are congruent with the previous findings involving sleep manipulations or IH models of OSA in rodents. Indeed, cognitive impairments have emerged with sleep deprivation by exploring different learning and memory test paradigms, such as the Morris water maze ( Nair et al, 2011a , 2011b ; Tartar et al, 2006 ; Xie et al, 2020 ), contextual fear conditioning ( Rossi et al, 2014 ; Sharma et al, 2021 ), inhibitory avoidance discrimination task ( Bueno et al, 1994 ; Perry et al, 2008 ) and the NOR test ( Djonlagic et al, 2012 ; Gozal et al, 2017 ; Kim et al, 2015 ; Palchykova et al, 2006 ). The latter NOR task has gained popularity in the investigation of memory alterations, since this test is based on the innate exploratory behavior of the rodent in the absence of externally applied rules or reinforcement ( Antunes and Biala, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work (Wellman et al, 2016) and the current study also demonstrate that individual outbred rats can show either decreases or increases in REM in response to IS, also without differences in freezing or SIH. Thus, while several studies have demonstrated that sleep may play a role in the consolidation of contextual fear memory associated with brief or mild fearful experiences (e.g., Graves, Heller, Pack, and Abel, 2003; Greenwood, Thompson, Opp, and Fleshner, 2014; Hagewoud, Bultsma, Barf, Koolhaas, and Meerlo, 2011; Hellman and Abel, 2007; Kumar and Jha, 2012; Menz, Rihm, and Büchel, 2016; Menz, Rihm, Salari, Born, Kalisch, Pape, Marshall, and Buchel, 2013; Rossi, Tiba, Moreira, Ferreira, Oliveira, and Suchecki, 2014; Silvestri, 2005; for recent review see Havekes, Meerlo, and Abel, 2015), there is no evidence that REM sleep is necessary for the formation of contextual fear memory associated with relatively intense stressful experiences. Interestingly, we found no correlation between freezing and either REM or NREM sleep.…”
Section: 0 Discussionmentioning
confidence: 99%